Hydroethanolic Extract from Bridelia atroviridis Müll. Arg. Bark Improves Haematological and Biochemical Parameters in Nicotinamide-/Streptozotocin-Induced Diabetic Rats. (26th November 2020) - Noussi Djouwoug, Clarice; Ngueguim, Florence Tsofack; Kamkumo Gounoue, Raceline; Donfack Gouni, Clémence; Kandeda, Antoine Kavaye; Philippe Djientcheu, Jean; Fifen, Rodrigue; Djomeni Dzeufiet, Desire Paul; Ngouela, Silvère; Sewald, Norbert; Lenta, Bruno Ndjakou; Dimo, Theophile
Abstract : Bridelia atroviridis Müll. Arg. (B. atroviridis ) is a plant used in Cameroonian traditional medicine to manage diabetes. The effects of hydroethanolic barks extract from B. atroviridis were evaluated on diabetes disorders including hematology, inflammatory, and oxidative stress parameters. The in vitro antioxidant capacity of the hydroethanolic bark extract (70 : 30) was evaluated. Nicotinamide-/streptozotocin-induced diabetic rats were daily treated with the B. atroviridis extract for fifteen days. Glycemia were evaluated every 5 days, insulin sensibility test was performed, and haematological, inflammatory, and oxidative stress parameters were analysed. Histomorphometry of the pancreas was realized. The extract was able to scavenge free radicals in vitro and decrease significantly the blood glucose levels. The treatment resulted in a significant alleviation of insulin resistance, anemia, leukocytopenia, and thrombocytopenia observed in untreated diabetic rats. The extract significantly decreased proinflammatory cytokines TNF- α, IL-1 β, and IL-10. The rate of reduced glutathione was increased in the pancreas, whereas the catalase activity and nitrite concentration were decreased. Diabetic control showed a reduced size of Langerhans islet, whereas the size of islets was large in treated groups. The hydroethanolic extract of B. atroviridis was able to improve glycemia and alleviate haematological and inflammatory parameters disorders observed in diabetic conditions, probably due to its antidiabetic, anti-inflammatory, and antioxidant capacities.